Supramolecular assembly of mebendazolium and dihydrogen phosphate ions in a new anthelmintic salt - Gutiérrez, Eduardo Luciano (2025)
A new mebendazolium dihydrogen phosphate phosphoric acid solid material was obtained and characterized by single-crystal X-ray diffraction and complementary solid-state techniques {systematic name: 5-benzoyl-2-[(methoxycarbonyl)amino]-1H-1,3-benzodiazol-3-ium dihydrogen phosphate–phosphoric acid (1/1), C16H14N3O3+·H2PO4−·H3PO4}. Structure solution confirmed proton transfer from phosphoric acid towards the basic imidazole ring of mebendazole. The mebendazolium cation and the dihydrogen phosphate anion assemble in the solid state in a cyclic hydrogen-bond-driven supramolecular motif, as observed in all mebendazolium/oxyanions structures reported in the literature. This salt crystallizes in the monoclinic P21/c (No. 14) space group. A detailed study of the crystal structure performed by atom-to-atom and global Hirshfeld surface analysis indicates that several hydrogen bonds act as the main intermolecular interactions stabillizing the material. The new material is stable up to 458 K.